EVALUASI SAMBUNGAN MUR-BAUT STRUKTUR PORTAL TRUSS “THE GREAT HALL” OBI ECO CAMPUS - JATILUHUR - Christian (Jurnal Riset Arsitektur, 2018)
Abstract- Bolt joint is one of the common joineries in a modern bamboo construction. The usage of the bolt joints in bamboo joinery are believed to be the most efficient therefore the bolt joint was used regardless of the various kind of different forces in every bamboo joinery. One of the disadvantage of the bolt joints in bamboo construction in the force that flow parallel to the bamboo fibers therefore some of joineries needed to be strengthen to prevent the joinery failure. The Great Hall OBI Eco Campus is one of the building which the joineries entirely connected by the bolt joints, through different forces in every joinery some of the joinery in the building are strengthen by rope. The bolt joints have many other combinations to strengthen the joinery that could be an option, they are bolt joint with clamping and with mortar injection. Key Words: Bolt Joint, parallel forcee to the bamboo fiber, strengthen by rope, “The Great Hall” OBI Eco Campus, Clamping, Mortar Injection